APLIKASI PENDEKATAN KESEIMBANGAN PORTOFOLIO TERHADAP NILAI TUKAR RUPIAH/DOLLAR AMERIKA - Nurbetty Herlina Sitorus (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2012)
Since the adoption of freely floating exchange rate system, the rupiah against the U.S. dollar continues to fluctuate. This has stimulated research on the instability of the rupiah and the factors that influence it. This study aims to analyze the variables that affect the exchange rate using the  portfolio balance approach. The portfolio balance approach is an extension of the monetary theory by incorporating a combination of assets other than domestic currency. The results  of the portfolio balance approach shows some variables that affect the exchange rate are Indonesia’s money supply (broad money), Indonesia’s net foreign assets and United States’ net foreign assets. It was also found that the speed of adjustment of the portfolio balance approach is 60,56. From this finding, it can shows that the portfolio balance model can be a good reference for explaining the movements of Indonesian Rupiah – US dollar exchange rate.